Método de integración de técnicas computacionales para el diseño y construcción de engranajes no metálicos del cuerpo de aceleración electrónico del vehículo CHEVROLET DMAX 2.4 l. - Agualongo Amangandi, Wilson Gabriel (2021)
The project focuses on the method of integrating computational techniques for the design and construction of non-metallic gears of the electronic throttle body of the Chevrolet DMAX 2.4 l vehicle, based on the use of new technologies focused on design and construction, applying CAD tools. , CAM, CAE, 3D printing, to convert physical or real models into digital 3D models; to determine the transmission ratio and the dynamic force of the spur gears, described under applied methodologies according to the different authors, such as Dvorak, Kelley and Faires, determining the need in the market, according to specialized technical processes, achieving excellence with marked values of 0 .25 according to the analysis of the obliquity mesh and 1, according to the study given by an orthogonal mesh, applying a torque of 5Nm, obtaining the best results determined in Nylon, which marked a deformation of 0.26, while in the resistance analysis 33.9 MPa is generated and in the FDS 4.04, which is a suitable value for a 3D printing process, according to the CAM procedure, through a direct interface that consists of additive manufacturing, which gives low costs, immediacy in the solution and reduction of waste, marking an appropriate margin of improvement which marks a weighting of 0.371.